Implementing digital finite impulse response filter using FPGA - Razak, Abdul Hadi Abdul; Zaharin, Muhamad Iqbal Abu; Haron, Nor Zaidi (2007)
This paper describes the design of Transposed Form FIR filter implemented in the Spartan-II and Virtex-E family of FPGAs. The design is an 8-tap filter based on 16-bit input samples and 14-bit signed coefficients.The basic building blocks of the filter are KCMs, Adders, Registers, and a delay-locked loop.All the 14-bit coefficient factors are stored with an 18-bit word size in the ROM.The program is written in VHDL source code based on application Xilinx notes [1] that describe the design of an FIR filter.The software tools have been used are Xilinx ISE Webpack 8.1, ModelSim 6.1e and Matlab 7.0.